Does wage-inflation targeting complement foreign exchange intervention? An evaluation of a multi-target, two-instrument monetary policy framework - XIE, Taojun (Institutional Knowledge at Singapore Management University, 2017)
We assess the inclusion of wage inflation as an intermediate target of an emerging central bank using a dynamic stochastic general equilibrium model with sticky wages and prices calibrated for the South Korean economy. The model includes wage inflation as an additional target jointly with domestic price inflation and the output gap in a Taylor- type interest rate rule operating with a sterilized foreign exchange (FX) intervention rule. Our results show a complementary relationship between wage inflation targeting and price inflation targeting. That is, by supplementing price inflation targeting with wage inflation targeting, welfare improves for cases with and without sterilized FX intervention. When intervention is in place, wage inflation targeting has the added advantage of reducing the volatilities of nominal exchange rate and foreign exchange reserves thereby promoting a more sustainable conduct of FX intervention.